Differential Expression of MicroRNAs in Response to Drought Stress in Maize - Jing-sheng LI; Feng-ling FU; Ming AN; Shu-feng ZHOU; Yue-hui SHE; Wan-chen LI (Journal of Integrative Agriculture, 2013)
Drought is one of the major abiotic stresses that limit maize productivity. Apart from the principal transcriptional regulation, post-transcriptional regulation mediated by microRNAs appears to be the prevalent response of plants to abiotic stress. In this study, the differential expression of microRNAs in the previously evaluated drought-tolerant inbred lines R09 under drought stress was detected by microarray hybridization. The target genes of the differentially-expressed microRNAs were predicted by bioinformatics software WMD3 for plant target gene prediction. The possible regulation of the differentially-expressed microRNAs as well as their target genes in maize response to drought stress was analysed according to Gene Ontology. Sixty-eight microRNAs in 29 microRNA families were detected to be differentially expressed in the seedling of the drought-tolerant inbred line R09, accounting for 5.97% of the total number of the probes. The expression profiles were different between the two time points of the drought stress. The functions of the genes targeted by the differentially-expressed microRNAs involve multiple physiological and biochemical pathways of response to abiotic stress, such as transcription regulation, metabolism, signal transduction, hormone stimulation, and transmembrane transport. Under drought stress, the differential expression of microRNAs regulates the expression of their target genes, resulting in multiple responses of physiological and biochemical pathways relative to drought tolerance of maize. miR156, miR159 and miR319 families may play more important roles. The different members of the same family may play similar regulation effects in most cases.